Quantification of Fines Migration in Block Caving Mining Through Laboratory Experiments - Vivanco-Avaria, F (Elsevier B.V., 2025)
The migration of fines in block caving mining corresponds to the movement of small-size granular material. This material is directed toward drawpoints, causing dilution of valuable mineral and safety concerns due to the formation of cohesive arcs. Although there are previous studies on the migration of fines through experiments with granular material and 3D simulations, empirical evidence is scarce. Therefore, a solid understanding of the relationship between variables affecting fines migration is lacking. Through experiments in a laboratory-scale physical model, the influence of different variables on the migration of fines is analyzed. The variables considered are the average diameter of the fine material, the content of the fine material, the orientation of the fine/coarse interface and the type of extraction. The results indicate that the migration of fines increases with a higher content of fine material and decreases with greater inclination, making these two variables the most significant. An interactive extraction reduces and delays the migration of fines to the extraction points. The average diameter of the fine material was shown to have a minor influence, which raises the possibility that the migration of fines depends on other variables, such as the uniformity coefficient, angle of repose, among others. The graphs obtained provide valuable information to understand the migration of fines in block caving operations under various conditions. The change in the migration of fines can be estimated by having different variables involved simultaneously. This is a complementary tool to the models currently used in mining to evaluate this phenomenon. © 2024 The Author(s)